The average rate of change obtained from the ratio of change in y to the change in x is 27
The average rate of change can be obtained using the relation :
Rate of change = (y2 - y1) ÷ (x2 - x1)
at; x1 = -3
y1 can be calculated from the function ;
y1= 3(-3³)-1
y1=-82
At ; x2 = 3
y2 can be calculated from the function ;
y2 = 3(3³)-1
y2=80
The rate of change can be calculated thus : (y2 - y1) ÷ (x2 - x1)
[80-(-82)]/[3-(-6])
162/6
27
Learn more about the average rate of change here:
brainly.com/question/18550782
#SPJ1
Answer:
9704.448
Step-by-step explanation:
(4.01)(10)−5
=35.1
(2.56)(108)
=276.48
(276.48)(35.1)
=9704.448
Answer:
I believe it's B!
Step-by-step explanation:
Not sure!!
Mean = (2+4+6+5+2)/5 = 19/5 = 3.8
answer
<span>C. 3.8</span>
Answer:
B
Step-by-step explanation:
x is the value of x which you input into the function and f(x) is the actual function and therefore the output. so when x=3, f(x)= -2. f(3)=-2